Early Childhood English Learning at The Naff Kindergarten: Pembelajaran Bahasa Inggris Anak Usia Dini di TK The Naff - Irwahani , Inama; DESTIANA, EVIE (Indonesian Journal of Education Methods Development, 2025)
General background: Early childhood is a critical period for language development, and exposure to foreign languages, particularly English, provides essential foundations for future communication. Specific background: In Indonesia, English is introduced as a foreign language from an early age, yet many schools still face challenges in implementation due to varying teacher competencies and parental awareness. Knowledge gap: Limited studies comprehensively describe the structured application of English learning in early childhood within bilingual school contexts. Aims: This study examines the implementation of English learning for children aged 5–6 years at The Naff A Creative & Fun School, focusing on teaching strategies, teacher competencies, and children’s achievements. Results: Data from structured and non-participant observations as well as semi-structured interviews show that children acquire basic vocabulary (colors, numbers, fruits, animals, etc.) and develop confidence in simple communication. Teachers play a central role through consistent routines, communication books, and bilingual classroom practices. Novelty: This study highlights how structured daily habituation combined with teacher preparation effectively fosters early English exposure in a playful yet systematic manner. Implications: Findings emphasize the importance of integrating bilingual practices into early childhood curricula and strengthening teacher qualifications to support sustainable language acquisition. Highlights: English learning at early age benefits from daily habituation. Teacher competence and creativity are crucial for successful practice. Bilingual strategies strengthen children’s vocabulary and confidence. Keywords: Early Childhood, English Learning, Bilingual Education, Teacher Competence, Language